The Cyclical Behavior of Capital Buffer of Indonesian Islamic and Conventional Banks - Atikah, Nur; Susamto, Akhmad Akbar; Saleh, Samsubar; Abdic, Ficrat (Universitas Muhammadiyah Yogyakarta, 2023)
This paper is aimed at analyzing the cyclical behavior of capital buffer of Islamic and conventional banks in Indonesia. More specifically, this paper has three objectives. First, to test whether capital buffer in Indonesian banking industry as a whole is countercyclical or procyclical. Second, to test whether there is a difference in the level of capital buffer of Islamic banks as compared to the level of capital buffer of conventional banks. Third, to test whether there is a difference in the cyclicality of capital buffer of Islamic and conventional banks. The analysis in this paper is conducted using the standard dynamic system generalized method of moments (system GMM) regressions and includes a panel of 108 banks over the period between 2004 and 2019. From the results, it can be concluded that the capital buffer of Islamic and conventional banks in Indonesia is procyclical. From the results, it can also be concluded that no difference exists in the level of capital buffer of Islamic banks as compared to conventional banks and in the cyclicality of capital buffer in Islamic and conventional banking. If the countercyclical capital buffer is achieved, a policy measure to alter the cyclical behavior of capital buffer of Islamic and conventional banks in Indonesia therefore is a must. Such policy measure needs not to be specified for Islamic or conventional banking industry.